2019
DOI: 10.1002/ange.201904191
|View full text |Cite
|
Sign up to set email alerts
|

Endlich homoleptisch: Synthese und vollständige Charakterisierung stabiler Salze des Mangantetranitrosylkations

Abstract: Trotz der ¾hnlichkeit zu Kohlenmonoxid ist die Chemie von homoleptischen Stickstoffmonoxidkomplexen im Unterschied zu ihren Carbonylanaloga bislang grundlegend unerforscht. Hier beschreiben wir die Synthese des ersten echten homoleptischen Übergangsmetallnitrosylkomplexes als Salz der schwachk oordinierenden Anionen (WCAs) [Al(OR F ) 4 ] À und [F{Al(OR F ) 3 } 2 ] À (R F = C(CF 3 ) 3 ). Diese Salze sind in guten Ausbeuten phasenrein zugänglichu nd wurden vollständig durch IR/Raman-, NMR-und UV/Vis-Spektroskopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…With that in mind, we made use of the versatility of carbon monoxide (CO) as a ligand by starting from Fe(CO) 5 as a Fe 0 source in combination with an oxidative approach. In order to compensate for the lability of the Fe À CO bond in the resulting iron cations, we utilized the weakly coordinating anion (WCA) [F-{Al(OR F ) 3 } 2 ] À (R F = C(CF 3 ) 3 ) [9,10] [11] In regard to ternary carbonyl/nitrosyl cations, the only currently known examples are [Cr(CO) 5 -(NO)][WCA], reported by us [12] and [Co(CO) 2 (NO) 2 ]-[WCA]. [13] And although the neutral Fe(CO) 2 (NO) 2 [14] and anionic [Fe(CO) 3 (NO)] À (the Hieber anion) [15] shown in Figure 1 were discovered more than half a decade ago and found their applications as useful starting materials or catalysts, [16] as of yet, their cationic counterparts have been mostly untouched.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…With that in mind, we made use of the versatility of carbon monoxide (CO) as a ligand by starting from Fe(CO) 5 as a Fe 0 source in combination with an oxidative approach. In order to compensate for the lability of the Fe À CO bond in the resulting iron cations, we utilized the weakly coordinating anion (WCA) [F-{Al(OR F ) 3 } 2 ] À (R F = C(CF 3 ) 3 ) [9,10] [11] In regard to ternary carbonyl/nitrosyl cations, the only currently known examples are [Cr(CO) 5 -(NO)][WCA], reported by us [12] and [Co(CO) 2 (NO) 2 ]-[WCA]. [13] And although the neutral Fe(CO) 2 (NO) 2 [14] and anionic [Fe(CO) 3 (NO)] À (the Hieber anion) [15] shown in Figure 1 were discovered more than half a decade ago and found their applications as useful starting materials or catalysts, [16] as of yet, their cationic counterparts have been mostly untouched.…”
mentioning
confidence: 99%
“…However, similar reactions showed that the more accessible alternative [Al-(OR F ) 4 ] À anion is not suitable for this system: although the [Fe(CO) 4 4 ]. [11] Therefore, we limit our report to the use of the more stable and less-symmetric [F-{Al(OR F ) 3 } 2 ] À anion. With this anion, the reactions in Scheme 1 led to phase-pure crystals of 1 and 2 (cf.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the identification of the crystals as 7 was unambiguous (molecular structure, see Figure 2). Presence of the assigned cationic species was verified by IR spectroscopic analysis showing a strong vibrational band of the single coordinated carbonyl moiety with a stretching frequency of 2057 cm À1 , which is, as expected due to the better WCA performance of our counterion, slightly (8). Data collected at 100 K. H atoms, counterions and (co-crystallized) oDFB were omitted for clarity.…”
Section: Resultsmentioning
confidence: 62%
“…However, the generated neutral NO is likely to undergo further ligand-substitution, for example, with transition-metal complexes. [8] Moreover, nitrosyl salts show a noticeable solvent dependency of their formal potential and are known to form colored charge transfer complexes with arenes as the first step towards electrophilic substitution, thus lessening their applicability. [9] Another class of deelectronating agents, and part of the work documented herein, are ammoniumyl radical cations, first observed over 100 years ago by Wieland.…”
Section: Introductionmentioning
confidence: 99%